2016
DOI: 10.1016/s2214-109x(16)30052-3
|View full text |Cite|
|
Sign up to set email alerts
|

Topical fluorouracil after surgery for ocular surface squamous neoplasia in Kenya: a randomised, double-blind, placebo-controlled trial

Abstract: SummaryBackgroundOcular surface squamous neoplasia (OSSN) is an aggressive eye tumour particularly affecting people with HIV in Africa. Primary treatment is surgical excision; however, tumour recurrence is common. We assessed the effect of fluorouracil 1% eye drops after surgery on recurrence.MethodsWe did this multicentre, randomised, placebo-controlled trial in four centres in Kenya. We enrolled patients with histologically proven OSSN aged at least 18 years. After standard surgical excision, participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…While we, like others, found no significant difference in outcomes between excisional biopsy vs chemotherapy, tumour extent (regardless of depth of invasion or treatment) seemed to play a role—as recurrent or persistent tumours were larger on average than tumours that did not recur. This trend toward larger size in recurrent tumours agrees with prior studies that have shown a significant relationship between increased recurrence and larger baseline tumour diameter …”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…While we, like others, found no significant difference in outcomes between excisional biopsy vs chemotherapy, tumour extent (regardless of depth of invasion or treatment) seemed to play a role—as recurrent or persistent tumours were larger on average than tumours that did not recur. This trend toward larger size in recurrent tumours agrees with prior studies that have shown a significant relationship between increased recurrence and larger baseline tumour diameter …”
Section: Discussioncontrasting
confidence: 56%
“…In our study, we found no significant difference in tumour outcomes when comparing invasive and non‐invasive lesions, even when primary treatment modality was accounted for. This is consistent with larger retrospective studies that found no significant difference in recurrence of invasive vs non‐invasive OSSN tumours . Additionally, a recent multicentre retrospective study demonstrated that tumour stage did not reliably predict initial treatment decisions, as both excision and chemotherapy were successfully utilized as treatment modalities for invasive and non‐invasive lesions, despite their histopathologic differences .…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…However, postoperative topical 5-FU drops have been shown to reduce the recurrence of OSSN in HIV patients. 52 , 90 …”
Section: Recurrence Of Ossn In Hiv Populationmentioning
confidence: 99%